2013
DOI: 10.3109/00016357.2013.764007
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-related osteonecrosis of the jaw in four Nordic countries and an indication of under-reporting

Abstract: Cumulative incidence of cases reported in this study differs to some degree in the four Nordic countries (Denmark < Finland < Norway < Sweden). In Norway, almost the same number of BONJ cases were reported through the questionnaire by OMS as in all four countries together (214 by OMSs vs 254 to MAs) and included a high number after per oral administration. The present results indicate a notable under-reporting in Norway and most likely in other Nordic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Under‐reporting is a well‐known limitation of pharmacovigilance databases and has been estimated to vary from 80 to 95% . Under‐reporting was also described for BRONJ in Norway . The estimated incidence of BRONJ by the Norwegian pharmacovigilance system was four times lower than the Norwegian OMS estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Under‐reporting is a well‐known limitation of pharmacovigilance databases and has been estimated to vary from 80 to 95% . Under‐reporting was also described for BRONJ in Norway . The estimated incidence of BRONJ by the Norwegian pharmacovigilance system was four times lower than the Norwegian OMS estimation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of reliable statistics indicating the number of patients exposed to BPs, it is still not easy to establish the real risk of developing BRONJ for non-cancer patients, also due to the large number of supposed and still unascertained risk factors. Moreover, some authors indicate a notable under-reporting [25] while affirming that BRONJ is becoming more common [30].…”
Section: European Journal Of Internal Medicine 24 (2013) 784-790mentioning
confidence: 99%
“…Sequential prescription of two different BPs prolonged the period of overall BP treatment until an ONJ occurred. Time of BP treatment keeping in mind that patients with ONJ that are treated outside of studies may benefit from fewer preventive dental treatments and are less likely to be reported to the authorities (Kruger et al 2013;Ulmner et al 2014).…”
Section: Introductionmentioning
confidence: 99%